Edukasi Penerapan Perilaku Hidup Bersih dan Sehat Sebagai Upaya Peningkatan Kesehatan pada Anak di Desa Denggungan Boyolali - Afrina Azra, Nur; Paramitha, Erina Adriana; Anisah, Mutiara; Nisa, Salma Fadila; Salma, Aini Dzuriyati; Aulia, Afifah Zakiyatul; Pahlavi, Arjuna Fatkhur Roziq; Waryati, Emy Tri; Adi, Wangsit Restu; Asyfiradayati, Rezania (Academia Publication, 2023)
Health education can create quality Human Resources (HR), health development is directed at efforts to increase awareness, willingness and ability to live healthily for everyone. To protect the body from disease and increase immunity, a clean and healthy lifestyle is very important in everyday life. The target of this activity is 25 children who are members of the At-Taqwa TPA in Denggungan Village, aged 2-15 years. Implementation of Clean and Healthy Living Behavior is a set of behaviors carried out on the basis of awareness as a result of learning. With this educational activity on establishing PHBS, it is hoped that the children of Denggungan Village will make clean and healthy living behavior a daily habit, both for themselves and for other people and the environment around them.